Penyuluhan Tentang Pencegahan Perilaku Vandalisme Melalui Peningkatan Wawasan Nusantara Pada Siswa Di Sekolah Menengah Pertama (SMP) Kartika Padang - Elwidarifa Marwenny; Rani Syafitri Rasyid; Nadya Maghfirah; Aulia Gading Pratiwi; Cinta Geovani; Muhammad Habil; Bisma Putra Zulkarnaen (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
Vandalism of public facilities is often caused by a lack of understanding among adolescents regarding national values and social responsibility. Observations in Padang City have shown that there are still public facilities that are damaged or polluted due to acts of vandalism committed by adolescents. As a preventive measure, a social action activity was carried out in the form of providing education through interactive socialisation through seminars and dialogues, with an approach tailored to the characteristics of students at SMP Kartika Padang. This c activity aims to analyze the effectiveness of socialisation based on increased wawasan nusantara in preventing vandalism among junior high school students. Increased understanding of the Wawasan Nusantara is expected to be a strategic foundation in building self-control and integrity among students, and can motivate students to become pioneer agents who can actively encourage their peers not to commit acts of vandalism.